2016
DOI: 10.1007/s00441-016-2448-0
|View full text |Cite
|
Sign up to set email alerts
|

Antennal-lobe tracts in the noctuid moth, Heliothis virescens: new anatomical findings

Abstract: As in other insects, three main tracts in the moth brain form parallel connections between the antennal lobe and the protocerebrum. These tracts, which consist of the antennal-lobe projection-neuron axons, target two main areas in the protocerebrum, the calyces of the mushroom bodies and the lateral horn. In spite of the solid neuroanatomical knowledge already established, there are still unresolved issues regarding the antennal-lobe tracts of the moth. One is the proportion of lateral-tract neurons targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 47 publications
8
30
2
Order By: Relevance
“…The lALT has previously been identified as a major output pathway for lcPNs (Homberg et al, 1988;Berg et al, 2007;Ian et al, 2016a,b). The current study confirms that pheromone-responsive lcPNs contribute to the lALT but also reveals that this tract bifurcates around the GC giving rise to ventral and dorsal pathways (Rø et al 2007;Ian et al, 2016b). Physiologically these PNs responded to single odorants but were characterized as blend enhanced.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The lALT has previously been identified as a major output pathway for lcPNs (Homberg et al, 1988;Berg et al, 2007;Ian et al, 2016a,b). The current study confirms that pheromone-responsive lcPNs contribute to the lALT but also reveals that this tract bifurcates around the GC giving rise to ventral and dorsal pathways (Rø et al 2007;Ian et al, 2016b). Physiologically these PNs responded to single odorants but were characterized as blend enhanced.…”
Section: Discussionsupporting
confidence: 81%
“…The morphology of the contralateral lcPN (Fig. 9E) is similar to ones previously reported in A. segetum (Wu et al 1996) and H. virescens (Ian et al 2016b). The axon of this PN followed the v-lALT ipsilaterally with no apparent synaptic contacts in the isthmus or along the ipsilateral process ( Fig.…”
Section: Contralateral Projectionssupporting
confidence: 85%
See 1 more Smart Citation
“…The second major target region for olfactory projections from the AL is the lateral horn ( Figure 6I). The neurons terminating in the lateral horn either originate in the medial antennal lobe tract and reach the lateral horn after providing input to the calyx, or they target this region directly via the lateral and mediolateral antennal lobe tracts (Ian, Berg, Lillevoll, & Berg, 2016). The lateral horn neuropil is located in the lateralmost part of the central brain and is medially completely fused with the surrounding protocerebral regions (inferior, superior and ventrolateral protocerebrum).…”
Section: Mushroom Bodiesmentioning
confidence: 99%
“…In a recent study of the heliothine moth, we demonstrated that the calyces get input mainly from the uni-glomerular PNs belonging to the medial ALT [16]. This kind of arrangement allowed us to measure odor-evoked activity from the medial-tract PNs specifically by applying the calcium-sensitive dye fura2 into the calyx.…”
Section: Introductionmentioning
confidence: 99%